Prognostic implications of global myocardial mechanics in hypertrophic cardiomyopathy by cardiovascular magnetic resonance feature tracking. Relations to left ventricular hypertrophy and fibrosis - Hinojar, Rocio; Fernández-Golfín, Covadonga; González-Gómez, Ariana; Rincón, Luis Miguel; Plaza-Martin, Maria; Casas, Eduardo; García-Martín, Ana; Fernandez-Mendez, Mª. Angeles; Esteban, Amparo; Nacher, Jose Julio Jimenez; Zamorano, Jose Luis (International journal of cardiology, 2017)
Interstitial fibrosis, myocardial fiber disarray and non-uniform shortening are common histological features of hypertrophic cardiomyopathy (HCM). The degree of LV hypertrophy and fibrosis are postulated to contribute to the impairment of myocardial shortening. Cardiovascular magnetic resonance myocardial (CMR) feature tracking (CMR-FT) has emerged as a robust method that provides quantitative measurements of myocardial deformation. Our aim was first to evaluate LV strain parameters in HCM by CMR-FT and their dependence on both functional parameters and late gadolinium enhancement (LGE); and secondly we sought to determine their association with major cardiovascular outcomes. 74 patients with HCM and 75 controls subjects underwent a CMR study including LGE imaging. Global peak longitudinal, circumferential and radial systolic strain values (GLS, GCS, GRS) were measured by CMR-FT. A primary endpoint of all-cause mortality and secondary combined endpoint of hospital admission related to heart failure, lethal ventricular arrhythmias or cardiovascular death were defined. Patients with HCM showed attenuation of all LV strain values (p<0.001). Multivariate analysis showed that both LV hypertrophy and %of LGE were independent predictors of attenuated LV strains. All systolic LV strain parameters were impaired in patients with primary and secondary endpoints (follow up time: 25.6±9.9months, p<0.05 and p<0.01 respectively). Abnormal GLS, GCS and GRS were significantly associated with primary and secondary endpoints. Both LV hypertrophy and fibrosis contribute to the impairment of LV myocardial mechanics in HCM. In this population, reduced LV strain is associated with poor cardiac outcomes, particularly cardiovascular mortality and HF.